Manifestasi Klinis Infeksi Mpox pada Penderita HIV: Sebuah Telaah Sistematik dan Meta-Analisis - Mardaningrat, Gede Ari Mahendra; Nugraha, Putu Arya; Putri, Isabella Soerjanto; Aryadi, Putu Hendri (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. Mpox is a zoonotic disease caused by the mpox virus. Sexual intercourse is the biggest cause of mpox transmission. Human immunodeficiency virus (HIV) is a viral infection that is also transmitted mostly through sexual routes. This systematic review and meta-analysis was conducted to understand the clinical picture of mpox in relation to HIV infection. Methods. This meta-analysis followed MOOSE (Meta-analysis of Observational Studies in Epidemiology) guidelines. A systematic search for relevant studies was carried out using the PubMed, EMBASE and Cochrane Library databases covering the period 1 January 2022 to 31 May 2024. The keywords used were “Clinical feature” or “Clinical Manifestation” and “MPOX” or Monkey pox and “HIV”. Results. There were 8 studies that met the inclusion and exclusion criteria for meta-analysis. Eight studies were identified with a total of 2,392 patients with and without HIV. In this meta-analysis, an analysis of each clinical manifestation appearing in patients was conducted, resulting in statistically significant findings, including lymphadenopathy (RR: 0.89; 95% CI: 0.82-0.96), perianal lesions (RR: 1.17; 95% CI: 1.01-1.37), proctitis (RR: 1.79; 95% CI: 1.37-2.35), rectal pain (RR: 1.33; 95% CI: 1.16-1.52), rectal bleeding (RR: 1.33; 95% CI: 1.16-1.52), and tenesmus (RR: 1.63; 95% CI: 1.34-1.99). Conclusions. Enlarged lymph nodes, perianal lesions, proctitis, rectal pain, rectal bleeding, and tenesmus are the dominant clinical manifestations in mpox patients accompanied by HIV infection.